1985
DOI: 10.1093/carcin/6.8.1127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ellagic acid and hydroxylated flavonoids on the tumorigenicity of benzo[a]pyrene and (±)-7β, 8α-dihydroxy-9α, 10α-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene on mouse skin and in the newborn mouse

Abstract: Ellagic acid, quercetin and robinetin were tested for their ability to antagonize the tumor-initiating activity of benzo[a]pyrene (B[a]P) and (+/-)-7 beta, 8 alpha-dihydroxy-9 alpha, 10 alpha-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (B[a]P 7,8-diol-9,10-epoxide-2), the ultimate carcinogenic metabolite of benzo[a]-pyrene. Ellagic acid, robinetin or quercetin (2500 nmol) had no tumor-initiating activity on mouse skin, but the topical application of 2500 nmol of ellagic acid 5 min before a tumor-initiating dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The observation that a dietary supplement of Q inhibits the development of 7,12-dimethylbenzanthracene and N-nitrosomethylurea induced rat mammary cancer (Verma et al, 1988) strongly support the possibility that Q could also be active in vivo. In addition Q and certain related flavonoids may be inhibitors of experimental skin carcinogenesis (Nakadate et al, 1984;Nishino et al, 1984;Chang et al, 1985). Although the mechanism of the antiproliferative activity of Q remains to be clarified, our data suggest that as in human breast cancer (Markaverich et al, 1988) and leukaemic cells (Larocca et al, 1990), this flavonoid may regulate cell growth through a binding interaction with type II EBS.…”
Section: Nm)mentioning
confidence: 68%
“…The observation that a dietary supplement of Q inhibits the development of 7,12-dimethylbenzanthracene and N-nitrosomethylurea induced rat mammary cancer (Verma et al, 1988) strongly support the possibility that Q could also be active in vivo. In addition Q and certain related flavonoids may be inhibitors of experimental skin carcinogenesis (Nakadate et al, 1984;Nishino et al, 1984;Chang et al, 1985). Although the mechanism of the antiproliferative activity of Q remains to be clarified, our data suggest that as in human breast cancer (Markaverich et al, 1988) and leukaemic cells (Larocca et al, 1990), this flavonoid may regulate cell growth through a binding interaction with type II EBS.…”
Section: Nm)mentioning
confidence: 68%
“…These mechanisms include spontaneous hydrolysis to tetrols and keto diols, non-enzymatic as well as enzymatic metabolism to triols and triol epoxides, hydration by epoxide hydrolase (EH) and glutathione (GSH) S-transferase (GST)-catalyzed conjugation with GSH (12)(13)(14)(15)(16)(17). In addition, certain plant phenols, such as ellagic acid, have been shown to inhibit mutagenic and carcinogenic effects of anti-BaPDE through direct interaction with this diol epoxide (18,19). Since BaPDE is a poor substrate for EH (20), the most important mechanism of BaPDE inactivation seems to be its conjugation with GSH.…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid (2,3,7,8-tetrahydroxy [J]benzopyrano [5,4,3-cde][J]benzopyran-5,10-dione), a natural product shikimate derivative present in soft fruits and vegetables (1-3), inhibits the carcinogenicity of benzo[a]pyrene (B[a]P) (4) and the carcinogenicity and mutagenicity (5)(6)(7)(8) and DNA binding (9,10) of benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide (BPDE), an activated form of B[a]P. It was suggested that the chemopreventive activity of ellagic acid results from its ability to accelerate the detoxification of BPDE by forming a BPDE-ellagic acid adduct (11). It was further suggested that the reason for the rapid reaction between BPDE and ellagic acid resulted from an initial ir-7r nonbonded interaction.…”
mentioning
confidence: 99%